632 Family History of Children Diagnosed with Obstructive Sleep Apnea. (3rd May 2021) - Porterfield-Pruss, Kristi; Willis, Denise; Spray, Beverly; Jambhekar, Supriya
Abstract: Introduction: Limited evidence suggests a familial association of OSA. It is not known how often children who require positive airway pressure (PAP) devices have a family member with OSA or that requires PAP. It is felt that PAP adherence in children is affected by PAP adherence in parents. We wanted to explore the relationship of OSA in children requiring PAP to OSA in immediate family members as well as the association of obesity and adherence between children and family members. Methods: Caregivers of children who utilize PAP devices at home were invited to complete an electronic questionnaire regarding family history of OSA. Descriptive statistics were utilized to summarize results. Results: The study was completed by 75 participants. The majority of children were male (64%, 48/75), black (47%, 35/75) and non-Hispanic (88%, 66/75). The mean age was 11.8 years (median 13) and mean BMI was 32.8 (median 29.8). The mean AHI on the diagnostic polysomnogram was 28.4 events per hour (median 15.3). Mean adherence to PAP > 4 hours per night was 56.5 (Median 68.2). Most, 87% (65/75), have other underlying medical problems. Twenty-four percent (18/75) have a biological father with OSA of whom 61% (11/18) are considered moderately/extremely obese. Of mothers, 13% (10/75) have OSA and 70% (7/10) are obese. Overall, 29% (22/75) had either a paternal (11%, 8/75) or maternal (19%, 14/75) grandfather with OSA of which 36% (8/22) are obese. For grandmothers, 31% (23/75) have OSA and 22% (5/23) are obese with more being paternal (19%, 14/75) compared to maternal (12%, 9/75). Of the 73 total family members reported to have OSA, 86% (63/73) use PAP and most (65%, 41/63) use it for > 4 hours every night. Few participants had siblings with OSA. Conclusion: There were more fathers with OSA than mothers, but mothers were reported to be obese more often. Grandparents were reported to have OSA but were reported to be obese less often than parents. Maternal grandparents with OSA were reported to be obese more than paternal grandparents. The majority of family members with OSA who use CPAP report nightly use. Support (if any):